Anathallis manausensis (Orchidaceae, Pleurothallidinae), a new species from the Brazilian Amazon - Krahl, Amauri Herbert; Valsko, Jefferson José; Holanda, Ana Sofia Sousa De; Chiron, Guy (Phytotaxa, 2016)
A new species is proposed in the genus Anathallis. It is described, illustrated and compared with its relatives. A key to the Amazonian species of Anathallis is presented. We propose a new combination in the genus Lankesteriana.